Sintezno proučevanje družbene kompleksnosti - primer vrednotenja politik - Radej, Bojan (Naše gospodarstvo, 2012)
Recognizing that the society has become complex means that the truth about social issues such as the identification of public interest or policy effectiveness is not a single truth (i.e., the official one in power); rather, a variety of well-founded and equally valid truths exist. Public management is complex; therefore, different views that do not share a common denominator should be regarded as incommensurable. Thus, it is necessary to examine the social phenomena in their duality between the interpretation of the primary meanings constituting the system as a whole, but in a deeply divisive way, and the interpretation of the secondary meanings of the evaluated social phenomenon, but only in the context of those not essential for anyone.
Keywords: družba; society; družbeni procesi; globalizacija; globalization